2003
DOI: 10.1287/orsc.14.5.574.16762
|View full text |Cite
|
Sign up to set email alerts
|

Constructing the Olympic Dream: A Future Perfect Strategy of Project Management

Abstract: In this paper we investigate a uniquely complex organizational context-that of the fast-tracked large-scale project management of a significant piece of Sydney 2000 Olympic infrastructure, which we researched in terms of its management through the "future perfect." In a grounded analysis we resolved to track how the future perfect developed in the life of one large, complex project whose uniqueness meant that it was unable to be strategically planned in advance. We tracked the use of what we term "future perfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
188
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(192 citation statements)
references
References 23 publications
2
188
1
1
Order By: Relevance
“…An emphasis on temporal work is especially relevant when actors would benefit from challenging received wisdom, reconsidering current concerns and engaging in an exploration of barely conceivable alternatives. This perspective reinforces the value of "framing experiments" (Schön and Rein 1994) and "strange conversations" (Pitsis et al 2003;Weick 1979) that allow practitioners to create breakdowns in their ingrained assumptions in order to reformulate problems at hand. Such interventions involve the construction of new strategic accounts that can prevent organizations from getting stuck in a strategy that is constrained by routinized understandings of the past, myopic views of the present, and limited visions of the future.…”
Section: Implications For Understanding Organizational Continuity Andmentioning
confidence: 61%
See 2 more Smart Citations
“…An emphasis on temporal work is especially relevant when actors would benefit from challenging received wisdom, reconsidering current concerns and engaging in an exploration of barely conceivable alternatives. This perspective reinforces the value of "framing experiments" (Schön and Rein 1994) and "strange conversations" (Pitsis et al 2003;Weick 1979) that allow practitioners to create breakdowns in their ingrained assumptions in order to reformulate problems at hand. Such interventions involve the construction of new strategic accounts that can prevent organizations from getting stuck in a strategy that is constrained by routinized understandings of the past, myopic views of the present, and limited visions of the future.…”
Section: Implications For Understanding Organizational Continuity Andmentioning
confidence: 61%
“…This gap has been noted recently by scholars who have suggested that an interpretive view of time might be useful in understanding organizational strategy making (Gioia et al 2002;Suddaby et al 2010;Tsoukas and Shepherd 2004). For example, the idea of future perfect thinking remains underdeveloped (Gioia et al 2002), meriting only a few pages in Weick's (1979Weick's ( , 1995 seminal works, and rarely taken up empirically (see Pitsis et al 2003, for an exception).…”
Section: Foundations For Understanding Temporal Work In Strategy Makingmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond complex projects, whose end-states can be specified at the outset but not their designs (Pitsis et al, 2003), are found organic projects whose endstates are often aspirational at the outset and can evolve unpredictably over time. For these organic projects, both their end-states and designs need to adapt to ongoing experience, learning, and resource availability, e.g., government programmes (Lindblom, 1979;Lundin and Söderholm, 2013).…”
Section: Understanding Project Knowledge -Traditional and Complexmentioning
confidence: 99%
“…As a result, infrastructure projects frequently run late, overrun budgets, and deliver outputs that leave many user groups and communities discontent (Morris 1994, Miller and Lessard 2001, Pitsis et al 2003, Esty, 2004, Gil and Tether 2011.…”
Section: Introductionmentioning
confidence: 99%